ART outcome in young women with premature ovarian aging - Meenakshi Dua; Vandana Bhatia; Sonia Malik; Ved Prakash (Wolters Kluwer Medknow Publications, 2013)
Background: Young women with signs of ovarian aging are a matter of concern as far as their reproductive performance is concerned. With more women approaching infertility centers with this problem, it becomes necessary to understand what reproductive outcomes are possible in such cases. Female age and basal Follicle stimulating hormone (FSH) level, both are strong independent predictors of In Vitro Fertilization (IVF) outcome. Objective: To correlate age-related basal FSH with IVF outcome in women with premature ovarian aging in gonadotropins-induced cycles. Materials and Methods: Between January 2011 and October 2012, a total of 135 women undergoing IVF and ICSI cycles with antagonist protocol were included in this retrospective cohort study. Basal FSH concentrations were measured and the women's ages were calculated before they were undergoing pituitary desensitization and its correlation with assisted reproduction technique (ART) outcome was evaluated. Results: Increasing FSH was associated significantly with reduced number of oocytes retrieved, and embryos obtained. Young women with high FSH up to 20 produced less but good quality embryo's resulting in sound pregnancy rate. Conclusion: FSH is a quantitative and age is a qualitative measure of ovarian reserve. Both are equally important in predicting IVF outcome. Basal FSH concentration should be restricted to counseling of patients on probability of achieving pregnancy, but should not be used to exclude them from fertility treatment.